Exploring the Work Immersion Experiences of Grade 12 STEM Students in a Local Science Integrated High School: A Narrative Research - Zohail I. Ador; Hyacinth Amanda C. Banaag; Claire Angela M. Bombio; Daphne Nicole A. Consignado; Marjanna Angelica V. Quinay; Justin Lemuel C. Santos (PT FORMOSA CENDEKIA GLOBAL, 2023)
The implementation of the K–12 curriculum in the Philippines brought about changes to the education system. One of which is the implementation of Work Immersion in senior high school. This is a subject that immerses students in different work environments. This narrative research was conducted to explore the experiences of senior high school students from a local science-integrated high school before, during, and after their Work Immersion. A semi-structured interview was held to gather data. Interviews were recorded and transcribed. Thematic analysis was used to identify themes that emerged from the study. Results revealed that the students’ have little to no idea about Work Immersion. Nonetheless, students stated that their experience in Work Immersion helped them enhance and prepare themselves for their careers. Lastly, the learning process gained from Work Immersion helped students for personal growth. The schools may find more partner institutions aligned with students’ interests and future careers for a more meaningful experience.